Seabuckthorn Pulp Oil Protects against Myocardial Ischemia–Reperfusion Injury in Rats through Activation of Akt/eNOS - Suchal, Kapil; Bhatia, Jagriti; Malik, Salma; Malhotra, Rajiv Kumar; Gamad, Nanda; Goyal, Sameer; Nag, Tapas C.; Arya, Dharamvir S.; Ojha, Shreesh (Frontiers in Pharmacology, 2016)
Seabuckthorn (SBT) pulp oil obtained from the fruits of seabuckthorn [Hippophae rhamnoidesL. (Elaeagnaceae)] has been used traditionally for its medicinal and nutritional properties. However, its role in ischemia-reperfusion (IR) injury of myocardium in rats has not been elucidated so far.The present study reports the cardioprotective effect of SBT pulp oil in IR-induced model of myocardial infarction in rats and underlying mechanism mediating activation of Akt/eNOS signaling pathway. Male albino Wistar rats were orally administered SBT pulp oil (5, 10and 20 ml/kg/day) or saline for 30 days. On the day 31, ischemia was induced by one-stage ligation of left anterior descending coronary artery for 45 min followed by reperfusion for 60 min. SBT pulp oil pretreatment at the dose of 20 ml/kg observed to stabilize cardiac function and myocardial antioxidants such as glutathione, superoxide dismutase, catalase and inhibited lipid peroxidation evidenced by reduced malondialdehyde levels as compared to IR-control group. SBT pulp oil also improved hemodynamic and contractile function and decreased tumor necrosis factor and activities of myocyte injury marker enzymes; lactate dehydrogenase and creatine kinase-MB. Additionally, a remarkable rise in expression of pAkt-eNOS, Bcl-2 and decline in expression of IKKβ/NF-κB and Baxwas observed in the myocardium. The histopathological and ultrastructural salvage of cardiomyocytes further supports the cardioprotective effect of SBT pulp oil. Based on findings, it can be concluded that SBT pulp oil protects against myocardial IR injury mediating favorable modulation of Akt-eNOS and IKKβ/NF-κB expression.